DESAIN BAHAN AJAR MELALUI MEDIA PODCAST DALAM PEMBELAJARAN PAI DI SMKN 13 BANDUNG - Neng Rina Rahmawati, - (2022)
Learning Islamic Religious Education should be able to answer the challenges of an all-digital era. Ideally, the teacher can package the material by utilizing technology to make it more attractive to students. Unfortunately, some teachers find it difficult to convey the material through internet-based media, causing students to feel bored and bored and even consider PAI subjects to be unimportant, especially during the covid pandemic where the use of technological devices is a necessity in the learning process. This study aims to describe the design of PAI teaching materials through podcast media in PAI learning in schools. Specifically, it aims to: 1) Describe the process of designing and packaging PAI teaching materials into a podcast in PAI learning at SMKN 13 Bandung 2) Describe the process of publishing podcasts in PAI learning at SMKN 13 Bandung, and 3) analyse student responses to podcast media that used in PAI learning at SMKN 13 Bandung. This study uses a qualitative descriptive-exploratory method. Researchers are the key instrument. Collecting data using interview techniques, observation, and documentation. Technical data analysis with reduction, display data, then conclusions. The results of the study show that podcasts can be used as learning media by designing teaching materials and social media publications. This was responded to by students positively by utilizing this learning podcast media.